Influencia del soporte familiar en la calidad de vida del adulto mayor del Centro del adulto mayor Salaverry, 2021 - Delgado Cosavalente, Ingrid Geraldine (2022)
The present investigation was carried out with the purpose of analyzing the influence of family support on the quality of life of the elderly of the active users of the Center for the Elderly, district of Salaverry, province of Trujillo. The sample consisted of 28 active users, in which the development of the research methods such as deductive, inductive, statistical and analyticalsynthetic were applied, as well as techniques such as the interview and the survey that were presented through the interview guide instruments, interview record and survey questionnaire, which were applied to older adults together with their families, arrived at qualitative and quantitative data allowing the analytical understanding of the indicators and their variables. According to the analysis carried out and the results obtained in the research, it is evident that family support positively influences the quality of life of older adults, based on optimal family relationships in 96% and the adequate social well-being of users with disabilities. 61% that occurs in the family; Likewise, family relationships are presented in the accompaniment with 86%, 100% in assertive communication and family participation in 89%, which significantly influences the quality of life of the elderly.